Interação da correção da acidez do solo com nitrogênio no acúmulo de carbono estável no solo - Andrade, Maria Gabriela de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The effect of the direct seeding system on the accumulation of carbon (C) in the soil is well known. The amount of labile C in the soil is related to the quantity and quality of straw in the system. However, the accumulation of stable C, linked to soil minerals, is more interesting due to its greater resilience. It is known that conservation production systems improve soil aggregation and that smaller aggregates accumulate stable C, which, in turn, depends on the nitrogen (N) present in the system and the presence of cationic bridges. Although the effect of each of these factors is known, little is known about the interaction between them. The objective was to study the effect of applying limestone and agricultural gypsum, associated or not with nitrogen fertilization, on soil aggregation, accumulation of C and humic substances, relating the accumulation of stable C with the classes of aggregates in a production system with soybeans and corn intercropped with Tanzania grass, in the second harvest. The field experiment was installed in Botucatu-SP, in 2016, and the data presented are from 2020 to 2022. The treatments were: control (without application of limestone and gypsum), limestone, and limestone + gypsum, with combined doses of N of 0, 80, 160, and 240 kg ha-1, applied annually to corn. Soybeans were grown in the spring/summer and corn in the fall/winter of each year. The combination of limestone, gypsum, and nitrogen fertilizer led to a 13% higher total C stock and a 20% higher total N stock in the 0-60 cm soil profile compared to the control. Liming + N reduced fulvic acids (FA) and humic acids (HA), but the application of gypsum mitigated this negative effect. The application of lime, gypsum, and N increased humin levels, mainly on the soil surface. Thus, the best strategy to increase C storage and stabilization in humid tropical soils in double soybean-corn cultivation was the combined use of limestone, gypsum, and nitrogen fertilizer applied to corn, achieving greater C storage in larger aggregates. The application of limestone and gypsum resulted in lower carbon mineralization compared to the control under N deficiency. N mineralization was greater when limestone + gypsum was applied together with N. Liming and nitrogen fertilization significantly increased nitrate levels in the soil, with no differences between liming and liming + plaster. Greater microbial activity, carbon mineralization, and nitrification were observed when N was applied to the soil. Furthermore, it was observed that the application of liming and liming + gypsum played a substantial role in the processes involving C mineralization in soils, with greater effects on smaller aggregates. Liming management and gypsum application can extend these benefits to deeper soil layers, resulting in increased soil fertility in subsurface layers. Soil management using limestone + gypsum proved to be a promising practice in increasing the productivity of soybeans and corn. Grains, especially at a lower dose of N (80 kg ha-1) or in the absence of nitrogen fertilizer. This result demonstrates the positive impact of liming and gypsum management on the N-use efficiency of crops, thus reducing dependence on nitrogen fertilization in acidic soils. Productivity gains were directly linked to the physical (greater stability and diameter of aggregates) and chemical (pH and macronutrient content) improvements in the soil provided by limestone + gypsum management. Therefore, it is concluded that the synergism of soil correction practices with liming, gypsum, and nitrogen fertilization applied to second-crop corn intercropped with forage species resulted in greater grain productivity, increased soil fertility, C sequestration, and storage, especially in larger aggregates.

É bem conhecido o efeito do sistema de semeadura direta no acúmulo de carbono (C) no solo. A quantidade de C lábil no solo tem relação com a quantidade e qualidade de palha do sistema. Entretanto, o acúmulo de C estável, ligado aos minerais do solo, é mais interessante devido à sua maior resiliência. Sabe-se que sistemas de produção conservacionistas melhoram a agregação do solo, e que agregados menores acumulam C estável, o que, por sua vez, depende do nitrogênio (N) presente no sistema e da presença de pontes catiônicas. Embora o efeito de cada um desses fatores seja conhecido, pouco se sabe sobre a interação entre eles. Objetivou- se estudar o efeito da aplicação de calcário e gesso agrícola, associados ou não à adubação nitrogenada, na agregação do solo, acúmulo de C e substâncias húmicas, relacionando o acúmulo de C estável com as classes de agregados em um sistema de produção com soja e milho consorciado com capim Tanzania, em segunda safra. O experimento de campo foi instalado em Botucatu-SP, no ano de 2016, e os dados apresentados são de 2020 a 2022. Os tratamentos foram: controle (sem aplicação de calcário e gesso), calcário, e calcário + gesso, com doses combinadas de N de 0, 80, 160, 240 kg ha-1, aplicadas anualmente ao milho. A soja foi cultivada na primavera/verão e o milho no outono/inverno de cada ano. A combinação de calcário, gesso e adubação nitrogenada levou a um estoque total de C 13% maior e um estoque total de N 20%maior no perfil de solo de 0-60 cm em comparação com o controle. A calagem + N reduziu ácidos fúlvicos (AF) e ácidos húmicos (AH), mas a aplicação de gesso mitigou esse efeito negativo. A aplicação de calcário, gesso e N aumentou os teores de humina, principalmente na superfície do solo. Assim, a melhor estratégia para aumentar o armazenamento e estabilização de C em solos tropicais úmidos no duplo cultivo soja-milho foi o uso combinado de calcário, gesso e adubação nitrogenada aplicada ao milho, alcançando maior armazenamento de C em agregados maiores. A aplicação de calcário e gesso resultou em menor mineralização de carbono comparado ao controle sob deficiência de N. A mineralização de N foi maior quando calcário + gesso foi aplicado junto com N. A calagem e a adubação nitrogenada aumentaram significativamente os níveis de nitrato no solo, sem diferenças entre calagem e calagem + gesso. Foi observada maior atividade microbiana, mineralização de carbono e nitrificação quando N é aplicado no solo. Além disso, observou-se que a aplicação de calagem e calagem + gesso desempenhou um papel substancial nos processos que envolvem a mineralização de C nos solos, com maiores efeitos em agregados menores. O manejo de calagem e aplicação de gesso pode estender esses benefícios para camadas mais profundas do solo, resultando em um aumento da fertilidade do solo nas camadas subsuperficiais. O manejo do solo utilizando calcário + gesso mostrou-se uma prática promissora no aumento da produtividade de grãos de soja e milho, especialmente na menor dose de N (80 kg ha-1) ou na ausência da adubação nitrogenada. Este resultado demonstra o impacto positivo do manejo da calagem e gessagem na eficiência de uso de N das culturas, reduzindo assim a dependência da adubação nitrogenada em solos ácidos. Os ganhos de produtividade foram diretamente ligados à melhoria física (maior estabilidade e diâmetro de agregados) e química (pH e teores de macronutrientes) do solo proporcionadas pelo manejo de calcário + gesso. Portanto, conclui-se que o sinergismo das práticas de correção do solo com calagem, gessagem e adubação nitrogenada aplicadas no milho segunda safra consorciado com espécie forrageira resultou em maior produtividade de grãos, incremento da fertilidade do solo, sequestro e armazenamento de C, especialmente em agregados de maior tamanho.
Interaction of soil acidity correction with nitrogen in stable soil carbon accumulation
Keywords: Nitrogen fertilization; Soil aggregates; Liming; Glycine max L; Zea mays L.; Adubação nitrogenada; Agregados de solo; Calagem